Monitoring forest degradation in Mexico based on the national forest and soil inventory (Infys) - Leyva Ovalle, Ángel; Valdez-Lazalde, José René; de los Santos-Posadas, Héctor Manuel; Martínez-Trinidad, Tomás; Herrera Corredor, José Andrés; Lugo Espinosa, Oziel; García Nava, José Rodolfo (Instituto de Ecología, A.C., 2017)
There are many definitions of forest degradation, however, most of them are not operational because they do not propose variables to measure it. Its measurement is complex. Evaluation involves comparing the status of the forest at a given time with a previous state (reference condition or baseline). The challenge to follow-up the degradation process begins with its definition and the identification of the baseline. The present paper proposes a General Index of Degradation (IGD, for its meaning in Spanish) to assess forest degradation that occurs in Mexico in the time period between measurements of the National Inventory of Forest and Soil (Infys). The IGD is composed of indicators that take as input the Infys database. At the same time, the study aims to build a base line that will allow monitoring forest degradation in future years. The results at the scale of federal entity indicate that the states of Puebla, Veracruz, Morelos and Colima show no evidence of degradation processes (IGD) during the period evaluated. On the contrary, Querétaro, Tamaulipas and Mexico City recorded certain process of degradation. The value of the IGD weighted at the national scale indicates that in general, for the five-year periods evaluated (e.g. 2004-2009, 2005-2010, etc.) the country’s ecosystems do not record any significant degradation, i.e., the value obtained from the IGD is equal to the baseline value. However, at the local scale it is possible to identify areas severely degraded or even deforested.